PERAN SEKTOR PERTANIAN DI PROVINSI JAWA TIMUR PADA SEBELUM DAN SETELAH PEMBERLAKUAN OTONOMI DAERAH - Gilang Wirakusuma; Hani Perwitasari; Irham Irham (MEDIAGRO, 2015)
This study aims to know agricultural sector/sub sector which have a role as leading  sector/sub  sector  in  East  Java  Province,  trend  of  contribution  of agricultural sector for GDRP and employment in East Java, determinant factor of agricultural  sector  growth.  Parameters  of  this  study  goals  are  divided  in  two periode,  those  periode  are  before  Local  Autonomy  era  and  during  Local Autonomy era. Analysis tools that used for this study are Location Quotient (LQ), Dynamic  Location  Quotient  (DLQ),  Shift-Share  Analysis,  and  Linear  Trend.Before  Local  Autonomy  era,  crop  plant  is  the  leading  sub  sector  for  East  Java Province.  Animal  husbandry  is  the  leading  sub  sector  for  East  Java  in  Local Autonomy  era.  This  study  show  that  national  economic  activity  is  the  most dominant  factor  for  agricultural  sector  growth  before  Local  Autonomy  era  and during  Local  Autonomy  era.  Trend  of  contribution  of  agricultural  sector  in employment  and  GDRP  show  the  declining  line.  Declining  agricultural  sector contribution in GDRP faster than it's contribution in employment.Keywords:  Determinant  factor  of  growth, local  autonomy, role  of agricultural sector.